Solid‐State Hydrogen‐Bond Alterations in a [Co2Fe2] Complex with Bifunctional Hydrogen‐Bonding Donors. Issue 31 (26th April 2019) - Nihei, Masayuki; Yanai, Yuta; Natke, Dominik; Takayama, Ryo; Kato, Marina; Sekine, Yoshihiro; Renz, Franz; Oshio, Hiroki
Abstract: A hydrogen‐bonding donor–acceptor system, [Co2 Fe2 (bpy*)4 (CN)6 (tp*)2 ](PF6 )2 ⋅2ABA⋅4BN⋅2PE (1 solv ), was prepared by co‐crystallization of an external stimuli‐responsive cyanide‐bridged tetranuclear [Co2 Fe2 ] complex and bifunctional hydrogen‐bonding donors, p ‐aminobenzoic acid. Compound1 solv exhibited a gradual electron‐transfer‐coupled spin transition (ETCST), and the removal of solvent molecules led to an abrupt thermal ETCST behavior with increased transition temperature. X‐ray structural analysis revealed that the modification of ETCST was caused by a significant alteration of a hydrogen‐bonding mode between the tetranuclear [Co2 Fe2 ] 2+ cations and ABA molecules. Variable temperature IR measurements indicated that the desolvated form, 1 desolv, showed dynamic alteration of hydrogen‐bonding interactions coupled with thermal ETCST behavior. These results suggested that the tetranuclear [Co2 Fe2 ] complex shows solid‐state modulations of hydrogen‐bond strengths by external stimuli. Abstract : Mixed‐valent compounds : A hydrogen‐bonding donor–acceptor system composed of external stimuli‐responsive [Co2 Fe2 ] 2+ cations showed solid‐state alterations of hydrogen‐bonding interactions induced by solvent release and thermal intramolecular electron transfers (see scheme).